Polymer-assisted deposition of SrTiO3 film as cathode buffer layer in inverted polymer solar cells. (December 2017) - Wang, Haizhen; Patterson, Brian; Yang, Jianzhong; Huang, Di; Qin, Yang; Luo, Hongmei
Graphical abstract: Highlights: SrTiO3 films on ITO-glass substrates have been prepared using polymer-assisted deposition (PAD) method. SrTiO3 films have been utilized as cathode buffer layer in inverted polymer solar cells with a power conversion efficiency of 2.96%. Further incorporation of MoO3 as anode buffer layer, the power conversion efficiency could be improved to 3.48%. Polymer-assisted deposition method would be a versatile approach for preparation of buffer layer materials in inverted polymer solar cells. Abstract: Polymer-assisted deposition (PAD) method has been employed to prepare SrTiO3 (STO) films on ITO substrates, which have been applied as cathode buffer layer in inverted polymer solar cells. ZnO and TiO2 films on ITO glass were also prepared via PAD and have been utilized as cathode buffer layers in the inverted polymer solar cells for comparison, which show better efficiency than those using ZnO and TiO2 as interfacial layers prepared through other methods. The power conversion efficiency (PCE) of ∼3.5% was achieved with STO as the cathode buffer layer as well as MoO3 as the anode buffer layer, which is comparable to that with ZnO and TiO2 prepared using the same method as cathode buffer layers. Our findings indicate that STO has the potential to be a candidate as interfacial layers in solar cell devices.